CHARACTERISTICS OF THE PROTECTIVE ANTIGEN COMPLEX OBTAINED FROM FRANCISELLA TULARENSIS SSP. NOVICIDA - E. M. Kuznetsova; O. A. Volokh; N. G. Avdeeva; Yu. I. Samokhvalova (Проблемы особо опасных инфекций, 2017)
F. tularensis ssp. novicida, considered earlier as a representative of a separate species, has been recently classed among F. tularensis variety, based on the results of comparative analysis of 16S-ribosomal RNA. Subspecies novicida can cause disease only in immunocompromised humans and is low virulent for rabbits. Despite this, high rate of homology of the nucleotide sequence of F. tularensis intraspecific taxon is established. Objective of the study is to obtain protective surface antigen complex from F. tularensis ssp. novicida Utah 112 (ATTC 15 482) cells and investigate its properties. Materials and methods. Protein, carbohydrate, and lipid content of the antigen preparation was measured using conventional colorimetric methods, SDS-PAGE was conducted according to U.Laemmli, and immunoblotting – to H.Towbin. For purification and molecular mass determination column chromatography was applied. Immune-chromatographic activity was analyzed by immune-enzyme assay. Immunogenicity of the produced preparation was tested on scrub white mice, with LD50 and ED50 calculated according to Karber’s method. Results and conclusions. Carried out has been comparative analysis of physical-chemical, antigenic and bio-chemical peculiarities of the protective antigen complex obtained from F. tularensis Utah 112 cells and equivalent antigen complex obtained from the vaccine strain – F. tularensis 15 NIIEG. Protectivity of the preparation has been tested through inoculation of the immunized white mice with virulent F. tularensis 503/840 strain. Demonstrated have been distinctive features of the new preparation, by structure and composition, as compared to similar antigen from the vaccine producer strain, as well as the slowdown of its immunochemical and protective activities.